The metaphysics of extrinsic properties - Hoffmann-Kolss, Vera (Metaphysical research ;, 2010)
This book aims to develop a philosophical theory of extrinsic properties - of properties whose instantiation by an object does not only depend on what the object itself is like, but also on features of its environment. Various accounts of the intrinsic/extrinsic distinction are analysed in detail, and it is argued that the most promising approach to defining this distinction is to consider extrinsic properties as a particular type of relational property. Moreover, it is shown that two key notions in the metaphysics of properties, the supervenience relation and the dispositional/categorical dis.